(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Simultaneous laparoscopic surgeries are among the extensive and complex surgeries. The advantages of simultaneous laparoscopic operations are as follows: simultaneous correction of two or more surgical diseases, with minimal hospitalisation and rehabilitation time, good cosmetic effect and reduced number of postoperative complications. However, despite the availability of real opportunities to provide the necessary amount of medical care to this category of patients and to achieve maximum medical, social and economic effect, only 1.5-6% of such patients undergo simultaneous laparoscopic operations.